Chronic knee pain demystified: the Pellegrini-Stieda syndrome case report - Samsudin, Suhaiza; L., Zhuang Li; J., Mohd Khairil Mustafa (UniKL, 2024)
This case report describes a man who initially presented to a primary care clinic with recurrent chronic left knee pain for four years. He had a history of trauma from a motor vehicle accident in 2002 and sustained left femur fracture with no knee injury and had undergone a left total hip replacement due to avascular necrosis of the femoral head. Physical examination did not reveal significant abnormality like arthritis, ligamentous injury, or tumour. There was no tenderness or bony irregularity noted at the medial side of the left knee. Over a four-year period, the patient's knee pain worsened and became increasingly dysfunctional. No X-ray was performed as the patient was just treated for musculoskeletal pain. A knee radiographic examination finally done during the latest visit to primary care raised, concern for a potential bone malignancy, leading to a referral to a tertiary centre. Further investigations, including a CT scan, raised suspicion of benign periosteal thickening and an avulsed fragment adjacent to the medial femoral condyle, where he was diagnosed with a chronic left medial collateral ligament (MCL) injury with a large concomitant Pellegrini-Stieda lesion and a chronic partial anterior cruciate ligament injury. This case highlights the diagnostic challenges at the primary care level in differentiating between a benign chronic MCL injury and other common causes of knee pain, as the presenting symptoms are similar. An accurate diagnosis can be achieved with a thorough history, clinical examination, and the use of additional imaging techniques. Prompt recognition of this uncommon knee problem is essential for delivering suitable therapy and preventing unwarranted delays in referral and treatments.